Taubenschlag R.: The Law of greco-roman Egypt in the light of the papyri - Lisowski, Zygmunt (Czasopismo Prawno-Historyczne, 1949)
Recenzja: Taubenschlag R.: The Law of Greco-Roman Egypt in the light of the Papyri (332 B. C. — 640 A. D.), New York 1944, str. 487.